The celestial empire path of the dragon (Virginia: Landmark Media Inc., 1994)
This program examines China's rlationship with its neighbours and with European nation. It report on how in the 20th century, China ancient glory gave way to a new form of government, as it finally adapted to the outside worlds.
Part 14 A nation of diversity
Executive producer, William J. Meabian
Keywords: China -- Foreign relations -- 20th century; China -- Social life and customs -- History